The Relationship Between Hardiness and Academic Stress Among Dental Health Students at Poltekkes Kemenkes Aceh - Husnia, Fikriatul; Safrilsyah, Safrilsyah; Ridha, Usfur; Rachmiana, Aida (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Hardiness among Dental Health students at Poltekkes Kemenkes Aceh plays an important role in coping with academic stress. When students possess low levels of hardiness in dealing with stress during their academic journey, their ability to manage academic stress decreases, which can have a significant impact on their future. Academic stress refers to an individual's perception of academic stressors and how they respond to them. Hardiness is a set of attitudes and coping skills that help individuals transform potentially threatening situations into opportunities for personal growth by finding meaning behind the circumstances around them. Through this process, individuals can maintain optimal performance even under pressure while preserving their well-being. This study aims to determine the relationship between hardiness and academic stress among Dental Health students at Poltekkes Kemenkes Aceh. The research employed a quantitative approach with a correlational method. The measurement instruments used were Maddi’s Hardiness Scale and Gadzella’s Academic Stress Scale. The study population consisted of 221 students, with a sample of 135 students selected using probability sampling with the stratified random sampling technique. Data analysis was conducted using the Spearman correlation test. The results indicated a significant negative relationship between hardiness and academic stress, meaning that the higher the level of hardiness, the lower the level of academic stress, and conversely, the lower the hardiness, the higher the academic stress.